SOURCES AS A MIRROR OF SOCIAL HISTORY - Maxliyo Misrbekova (Modern American Journals, 2025)
This article analyzes the relationship between the theory of historical knowledge and ideological approaches. It highlights how, during the Soviet era, the science of history was divided into two major directions—Soviet and Western historiography—focusing on their conflicting methodologies and scientific perspectives. The article reveals how Soviet historiography was conducted under ideological pressure, often distorting historical truth. The religious and idealistic foundations of the philosophy of history in Western historiography, particularly through Augustine’s theory of linear history, are examined. Furthermore, the current stage of Uzbek historiography is evaluated from a comparative perspective with the historical thought of neighboring countries, emphasizing its pursuit of accuracy and objectivity. The article substantiates the necessity for history as a science to be free from ideology and underlines the decisive role of impartiality in historical knowledge.
Keywords: Historiography, Soviet science, Western science, ideology, historical knowledge, Augustine, philosophy of history, methodology, impartiality, ideological pressure, Uzbek historiography.